Rapid Aldosterone-Mediated Signaling in the DCT Increases Activity of the Thiazide-Sensitive NaCl Cotransporter - Cheng, Lei (J Am Soc Nephrol, 2019)
BACKGROUND: The NaCl cotransporter NCC in the kidney distal convoluted tubule (DCT) regulates urinary NaCl excretion and BP. Aldosterone increases NaCl reabsorption via NCC over the long-term by altering gene expression. But the acute effects of aldosterone in the DCT are less well understood. METHODS: Proteomics, bioinformatics, and cell biology approaches were combined with animal models and gene-targeted mice. RESULTS: Aldosterone significantly increases NCC activity within minutes in vivo or ex vivo. These effects were independent of transcription and translation, but were absent in the presence of high potassium. In vitro, aldosterone rapidly increased intracellular cAMP and inositol phosphate accumulation, and altered phosphorylation of various kinases/kinase substrates within the MAPK/ERK, PI3K/AKT, and cAMP/PKA pathways. Inhibiting GPR30, a membrane-associated receptor, limited aldosterone’s effects on NCC activity ex vivo, and NCC phosphorylation was reduced in GPR30 knockout mice. Phosphoproteomics, network analysis, and in vitro studies determined that aldosterone activates EGFR-dependent signaling. The EGFR immunolocalized to the DCT and EGFR tyrosine kinase inhibition decreased NCC activity ex vivo and in vivo. CONCLUSIONS: Aldosterone acutely activates NCC to modulate renal NaCl excretion.